Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Kinerja Karyawan Galeri Ekspedisi Surabaya - Zanetta Najlaa Putri Arfi; Kustini Kustini (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine the effect of organizational commitment and job satisfaction on employee performance at the Surabaya Expedition Gallery. This study uses a quantitative approach using SmartPLS software to analyze. The study population was 39 employees and the sampling technique used the saturated sample method because all members of the population were used, namely 39 respondents. Data collection was carried out through interviews, surveys and questionnaires. Data analysis includes validity and reliability tests, R-Square tests, and bootstrapping hypothesis tests. The results showed that organizational commitment and job satisfaction have a positive and significant effect on employee performance at the Surabaya Expedition Gallery.